HUBUNGAN POLA ASUH TERHADAP SELF CONCEPT PELAKU PERUNDUNGAN DEWASA AWAL - Aditama Pramono Jati; Untung Subroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The phenomenon of bullying is still going on and growing, one of the factors that greatly affect is the parenting of parents and the formation of individual self-concept in the bully. This study aims to determine the relationship between parental parenting with self-concept in perpetrators of bullying in early adulthood. This study used correlational quantitative methods with Purposive Sampling sampling techniques involving 130 participants aged 18-30 years who were actively bullying or had been bullying for at least the last three months. The instruments used were the Parental Authority Questionnaire (PAQ) and the self-report bullying perpetrator Questionnaire (SRBPQ). The results of the analysis showed that parental parenting has a positive and significant relationship with Self-Concept (r = 0.425, p = < 0.01) in abusers.